The environmental impact of cities death by democracy and capitalism - Chicca, Fabricio; Vale, Brenda; Vale, Robert (Robert James Dennis) (New York Routledge, 2023)
"The Environmental Impact of Cities assesses the environmental impact that comes from cities and their inhabitants, demonstrating that our current political and economic systems are not environmentally sustainable because they are designed for endless growth in a system which is finite. It is already well documented that political, economic and social forces are capable of shaping cities and their expansion, retraction, gentrification, re-population, industrialization or de-industrialization. However, the links between these political and economic forces and the environmental impact they have on urban areas have yet to be numerically presented. As a result, it is not clear how our cities are affecting the environment, meaning it is currently impossible to relate their economic, political and social systems to their environmental performance. This book examines a broad selection of cities covering a wide range of political systems, geography, cultural backgrounds and population size. The environmental impact of the selected cities is calculated using both Ecological Footprint and carbon emissions, two of the most extensively available indices for measuring environmental impact. The results are then considered in terms of political, economic and social factors to ascertain the degree to which these factors are helping or hindering the reduction of the environmental impact of humans. This book will be of great interest to students and scholars of sustainability, urban planning, urban design, environmental sciences, geography and sociology"--
Includes bibliographical references and index.
Keywords: City planning -- Environmental aspects; Cities and towns -- Growth -- Environmental aspects